Accommodating Digital Transformation in Sharia Financing of Sharia Financial Institutions: Indonesian Case - Amani, Shofia Naila; Woro Nilam Lestari; Yeni Nurjanah (Islamicate Institute, 2023)
Transformation in the Digital Age has emerged as a pivotal focus within the global financial sector, particularly concerning sharia financing. With technology advancing rapidly, Sharia financial institutions encounter novel challenges in upholding sharia principles while integrating digital solutions. This study endeavors to scrutinize the ramifications of digital transformation on sharia financing practices and delve into the adaptation strategies employed by sharia financial institutions to confront these changes. Employing qualitative research methods, this investigation synthesizes a myriad of scholarly sources alongside insights from sharia financial institutions, sharia scholars, and financial technology experts. The findings underscore the imperative for a coherent regulatory framework that accommodates digital transformation in sharia financing. Moreover, enhancing public education and comprehension concerning digital sharia financing emerges as a pivotal concern to expedite technological adoption and ensure the enduring viability of this transformation.